PENJADWALAN TENAGA KERJA UNTUK TIGA SHIFT DI PT. XYZ DENGAN PENGEMBANGAN METODE ALGORITMA TIBREWALA, PHILIPPE DAN BROWNE - Indriastiningsih, Erna (JURNAL GAUNG INFORMATIKA, 2015)
Labor scheduling is the allocation of human resources to work stations in accordance with needs, to increase productivity of the company must schedule labor optimally, PT XYZ is a packaging company located in Tangerang-Banten.The company has implemented workforce scheduling with 3 work shifts and 1 day off in 1 week.Human resources are very important to note, therefore, to increase company productivity there needs to be an additional day off for every workforce. To accommodate 3 work shifts per day and 2 days off in 1 week, this study uses the modified Tibrewala, Philippe and Browne algorithm methods. Modification of the algorithm changes and adds from 3 steps to 5 steps and changes the tabular table format for scheduling workers for three shifts. Scheduling workforce with 5 working days and 2 holidays requires a workforce of 20 people in the printing department and 26 people in the laminate section and 32 people in the Slitting section. The excess labor that occurs is 1 man-days in the printing section and 4 man-days on the laminate section, and 13 man days on the slitting section. The excess of the workforce can be  utilized when there are workers who do not enter work due to illness, permission or leave. The scheduling is expected to be able to maintain the health and safety of the workforce so that it can perform optimal work to increase the productivity of the company.